The Association between Placental Histopathology, Fetal Growth Restriction, and Preeclampsia in Twin Pregnancies - Matthews, Kathy C.; Fox, Nathan S.; Rebarber, Andrei (American Journal of Perinatology, 2019)
Objective This study aims to estimate the association between abnormal placental histopathology, fetal growth restriction (FGR), and preeclampsia (PEC) in twin pregnancies.Study Design Retrospective cohort study of women with diamniotic twin pregnancies with live births at ≥24 weeks of gestation and available placental pathology. Findings were compared between women with and without FGR, which was defined as a birthweight <10th percentile, using singleton and twin growth curves, and those with and without PEC. The primary study outcome was a composite of abnormal placental histopathology. Chi-square, Fisher's exact, and Student's t-tests were used for analysis.Results Among 859 patients with diamniotic twins, 806 (93.8%) had placental pathology. A total of 422 (52.4%) women had at least one twin with FGR, using a singleton growth curve. FGR affected 136 (16.9%) pregnancies when a twin growth curve was applied. There was no significant difference in composite outcome between groups, using either growth curve (45.5 vs. 44.8%, p = 0.84; adjusted odds ratio (aOR): 1.06, 95% CI: 0.79–1.40 and 52.2 vs. 43.7%, p = 0.07; aOR: 1.44, 95% CI: 0.90–2.10). A total of 122 of 789 (15.5%) patients developed PEC. There was no significant difference in composite outcome between patients with and without PEC (41.8 vs. 45.4%, p = 0.46; aOR: 0.79, 95% CI: 0.53–1.18).Conclusion In twin pregnancies, FGR and PEC are not associated with abnormal placental histopathology. This suggests that the pathologic placental manifestations of these conditions may differ in twins and include factors other than those commonly described in singletons.
Keywords: fetal growth restriction; histopathology; multiple gestation; pathology; placenta; preeclampsia; small for gestational age; twins